2015
DOI: 10.1039/c4mt00260a
|View full text |Cite
|
Sign up to set email alerts
|

Zinc isotopic compositions of breast cancer tissue

Abstract: An early diagnostic biomarker for breast cancer is essential to improve outcome. High precision isotopic analysis, originating in Earth sciences, can detect very small shifts in metal pathways. For the first time, the natural intrinsic Zn isotopic compositions of various tissues in breast cancer patients and controls were determined. Breast cancer tumours were found to have a significantly lighter Zn isotopic composition than the blood, serum and healthy breast tissue in both groups. The Zn isotopic lightness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 25 publications
3
98
1
Order By: Relevance
“…[1][2][3] Recent studies have shown the great potential of stable metal isotopes to identify contaminant sources, 4,5 to constrain biogeochemical processes during nutrient cycling, 6 weathering 7,8 and to reconstruct metal transfer processes in complex systems such as the human body. 9,10 Special attention has been given to Zn due to its key function as micronutrient in the biosphere and as pollutant in industrial, mining and urban environments. [1][2][3]11 The natural variations in the Zn isotopic composition are small (< 1‰), requiring reliable analytical procedures including chromatographic separation of Zn from the matrix [12][13][14] and accurate correction of the instrumental mass bias.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recent studies have shown the great potential of stable metal isotopes to identify contaminant sources, 4,5 to constrain biogeochemical processes during nutrient cycling, 6 weathering 7,8 and to reconstruct metal transfer processes in complex systems such as the human body. 9,10 Special attention has been given to Zn due to its key function as micronutrient in the biosphere and as pollutant in industrial, mining and urban environments. [1][2][3]11 The natural variations in the Zn isotopic composition are small (< 1‰), requiring reliable analytical procedures including chromatographic separation of Zn from the matrix [12][13][14] and accurate correction of the instrumental mass bias.…”
Section: Introductionmentioning
confidence: 99%
“…The isotopic fractionation of medium-mass endogen elements (i.e., Ca, Fe, Cu, and Zn) has recently been shown to have an outstanding potential for biomedical applications (1). Isotopic fractionation measurements have been identified as new biomarkers for the investigation of metabolic processes (2-6) and as powerful tools for the early detection of diseases (7)(8)(9)(10)(11)(12). Studies of Cu and Zn isotopic fractionation are very promising for the early diagnosis of different types of cancer (9,12) and neurodegenerative diseases (8,13), whereas Fe and Ca isotopic fractionation measurements have shown their ability to monitor Fe absorption efficiency (3) and bone mineral balance (7), respectively.…”
mentioning
confidence: 99%
“…Although no tumour tissue was analysed, Telouk et al suggest that isotopically heavy tumours relative to healthy tissue are likely due to the observed lighter Cu serum values in colorectal and breast cancer relative to healthy serum. The single tumourhealthy tissue couple presented by Larner et al shows that this may not be the case for early stage breast cancer, where the tumour tissue is −0.4 ‰ relative to adjacent healthy breast tissue [18]. Balter et al [21] found that both copper and sulfur isotopes of red blood cells were isotopically lighter for HCC patients relative to controls and suggested that sulfur blood isotopic analyses may provide a new diagnostic tool for HCC.…”
Section: Isotope Fractionation and Cancermentioning
confidence: 96%
“…The calcium serum isotopic composition has been found to have a significant relationship with myeloma (cancer of bone marrow) and implicates a new and needed method to evaluate real-time myeloma-induced bone disease [17]. Four further studies utilising natural isotopic analyses of zinc [18], copper [19][20][21] and sulfur [21] in cancer have emerged recently. Larner et al [18] found an isotopic enrichment in the lighter isotopes of zinc for breast tumours relative to healthy breast tissue in early stage breast cancer.…”
Section: Isotope Fractionation and Cancermentioning
confidence: 97%
See 1 more Smart Citation